2009
DOI: 10.4186/ej.2009.13.3.45
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical and Rheological Behaviours of Waste Glass Fibre-Filled Polypropylene Composites

Abstract: The composites between the reinforced glass fibre wastes obtained from surfboard manufacturing industry and polypropylene were developed for value adding and environmental reasons. The thermomechanical and rheological behaviours of the composites were investigated. Glass fibre contents were varied from 5 to 30wt%. The effects of maleic anhydride grafted polypropylene (MA-PP) compatibilizer on the behaviours were also determined. The results revealed that the addition of glass fibre was able to reduce the heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…In the same vein, Tiptipakorn et al found that the complex viscosity of PP composite reinforced with 20 wt% of GFs increased after the addition of 5% PP‐g‐MA, confirming the enhancement of fiber matrix interfacial adhesion and hence the lead transfer. However, the results of their rheological studies were able to provide the apparent flow activation energy which could reveal that the fluidity of the molten composites materials could be improved by using PP‐g‐MA.…”
Section: Resultsmentioning
confidence: 88%
“…In the same vein, Tiptipakorn et al found that the complex viscosity of PP composite reinforced with 20 wt% of GFs increased after the addition of 5% PP‐g‐MA, confirming the enhancement of fiber matrix interfacial adhesion and hence the lead transfer. However, the results of their rheological studies were able to provide the apparent flow activation energy which could reveal that the fluidity of the molten composites materials could be improved by using PP‐g‐MA.…”
Section: Resultsmentioning
confidence: 88%
“…The activation energy of viscous flow is historically derived from thermodynamic considerations. Flow is seen as a local transition of a molecule or a group of molecules between one state (position before flowing) to another (position after flow occurred) having to overcome an energy barrier [40][41][42][43]. For polymer solutions, the activation energy thus inevitably increases as the polymer concentration gets larger.…”
Section: Viscosity-temperature Dependencementioning
confidence: 99%
“…KMnO 4 treated CS also showed improvement in tensile properties because of grafting PP chains on CS fiber surface by the action of highly reactive Mn 3+ ions. These forms complex with –OH of cellulose and these species initiate the grafting reaction . This would increase the interaction of CS matrix very effectively.…”
Section: Resultsmentioning
confidence: 92%
“…Silane treated cotton stalk composite SCS have highest values of elastic modulus and PCS, KCS, ACS and NCS have nearly similar modulus values. The increase in elastic modulus is due to the better stress transfer at the interface which is combined of compatibilizer and chemical treatment of CS as SCS also showed highest tensile strength . No huge difference was observed in the viscoelastic behavior of all bio‐composites over the whole frequency range which indicates that the chemical treatment and addition of MAH‐g‐PP did not affect the morphology of the PP‐CS system.…”
Section: Resultsmentioning
confidence: 99%